Security Analysis and Portfolio Management - Punithavathy Pandian (New Delhi, 2024)
In the current scenario, investing in the stock markets poses a significant challenge even for seasoned professionals. Not surprisingly, many students find the subject Security Analysis and Portfolio Management difficult. This book offers conceptual clarity and in-depth coverage with a student-friendly approach. Targeted at the postgraduate students of management and commerce, it is an attempt to demystify the difficult subject. The book is divided into three parts. Part I explains the Indian stock market; Part II exclusively deals with the different aspects of security analysis; Part III is devoted to portfolio analysis.
English
Keywords: Economics; Portfolio Management; Security Analysis